Digital Innovation Based on Village Mall Application in the Development of Sidomulyo Tourism Village, Silo District Jember Regency - Qadiri, Fajri Salamil; Wicaksono, Itok (Journal of Geosciences and Environmental Studies, 2024)
The purpose of this study is to investigate and analyse the influence of digital innovation, specifically the Malldesa application, on tourism village development in Sidomulyo Village, Silo Sub-district, Jember Regency. Malldesa is developing tourism communities in Sidomulyo Village, Silo District, Jember Regency. The research method employed is qualitative, including observation techniques, in-depth interviews, and document analysis as the primary data sources. Malldesa management, community leaders, local officials, and visitors are among those who responded to the research. The findings revealed that the Malldesa application favourably impacted the growth of tourist communities in Sidomulyo Village. This program facilitates transactions, promotes local products, and broadens market reach for village businesses. Malldesa has also helped villages improve their information technology skills and comprehend the value of branding and digital marketing. Furthermore, this digital innovation has increased community participation in tourism village administration. Community participation in decision-making and development planning in tourist villages has expanded, improving collaboration between local governments, business actors, and communities. Thus, this study shows that digital innovation based on the Malldesa application plays a vital role in the development of tourism villages in Sidomulyo Village, Silo District, and Jember Regency. Information technology in the tourist sector can be one of the answers to improving the welfare of rural populations and advancing the area's tourism potential.